Histopathological And Biochemical Studies Of Etoposide Treated Liver Of Rat - PRATIBHA RAVINDRA; SAMEER R. KULKARNI; C. Y. DHUME; D. A. BHIWGADE (International Journal of Pharma and Bio Sciences, 2012)
Etoposide is a known anticancer drug used for treatment of various tumors. Studies were performed on rats treated with etoposide for 8 weeks. Histopathological alterations like parenchymal ruptures and vacuolation of hepatocyte were observed. The blood sinusoids were dilated and the central blood vessels were also congested with amorphous material. Transmission electron microscopic (TEM) observations showed vesicuolation of smooth and rough endoplasmic, electron dense mitochondria with intact matrix and presence of active golgi apparatus with its characteristic secretory granules and lipid vacuoles. Biochemical findings indicated a significant change in glutathione-s-transferase (G-ST), glutathione reductase (GR), catalase, cytochrome P450 (CYP450) and cytochrome b5 (CYP b5). However glutathione (GSH), glutathione peroxidase (GPx) and gamma glutamyl transferase (GGT) showed non-significant change. No significant increase was manifested in lipid peroxidation (Lpx) levels in the liver. The metabolic activation of drug by CYP450 displayed significant increase and significant decrease of CYP b5.These changes demonstrate that etoposide at given dose level is not involved in exerting cytotoxic action on the liver.